How Creativity Was Affected by Environmental Factors and Individual Characteristics: A Cross-cultural Comparison Perspective. Issue 3 (2nd July 2016) - Deng, Lifang; Wang, Lijuan; Zhao, Yanyun
Abstract : The purpose of this study was to explore how environmental factors (family environment and school education) and individual characteristics (personality, creative attitudes, and divergent thinking) collectively affect creative achievement of American and Chinese college students. Data were collected from 378 college students in the United States ( N = 193) and China ( N = 185). Results showed that the US sample had significantly higher means in home resources, high-school education, Conscientiousness, creative achievement, and all four dimensions of the Abbreviated Torrance Test for Adults (ATTA) than the China sample. In contrast, the China sample scored significantly higher in understanding the importance of creativity. Results indicated creative attitudes and divergent thinking sequentially mediated the effects of parental values on creative achievement for the US sample, whereas Openness mediated the effect of high-school education on creative achievement for the China sample. For both samples, creative attitudes mediated the effect of Openness on divergent thinking. The results suggested cultural differences in the effects of environmental factors on creativity, yet more similar findings in the effects of individual characteristics on creativity between the two samples. The results and implications are discussed.